Optimizing the Performance of Bhabinkamtibmas in Implementing Counseling Guidance to Prevent Youth Violence at Tegal Police - Jerico Pattimura (Tanggon Kosala, 2022)
This thesis discusses the optimization of the performance of bhabinkamtibmas in carrying out extension guidance to prevent acts of youth violence at the Tegal Police. Writing this final project has two objectives. The first is to describe the organizational resources of the bhabinkamtibmas performance in binluh activities to prevent acts of youth violence. second, describing the optimization of the performance of bhabinkamtibmas in implementing binluh to prevent acts of youth violence at the Tegal Police Station. The background for conducting this research is the high vulnerability of youth acts of violence at the Tegal Police Station which is marked by the fatality of these acts of violence where victims of juvenile violence suffer losses to death and the increase in the number of youth violence at the Tegal Police Station drastically from the previous year. This research was conducted using a qualitative approach to the type of research field research. The data obtained comes from primary and secondary data. Primary data were obtained through interviews, observation, and focus group discussions (FGD). Meanwhile, secondary data was obtained from existing documents at the research location. The concepts used in this study are the concepts of optimization, performance, bhabinkamtibmas, and youth violence. The theory used is the theory of SWOT analysis, POAC, and 6M. The results of this study are that the organizational resources and performance system of binluh that have been carried out by bhabinkamtibmas have not been optimal. The conclusion from this study is that there are still many aspects that need to be optimized in extension guidance by bhabinkamtibmas in order to prevent acts of youth violence at the Tegal Police Station both from organizational sources and performance systems.